SYSTEM ADMINISTRATION AND REGISTRATION OF PATIENTS IN CLINICAL TREATMENT USING VISUAL BASIC KARUNA MEDIKA 6.0 - Liza Poerwitasari; Eko Hadiyanto, SSI, MMSI Eko Hadiyanto, SSI, MMSI (Jurnal Sistem Informasi, 2002)
At the clinic in the registration section Medika Karuna as patient data which stillaccounted for using the book as a tool accessories. It takes a long time in therecording of patients who would enroll. To overcome this should be necessary tohave a computerized system so that it can accelerate the process of patient registrationand the reports will be submitted to the leadership and facilitate the archiving ofpatient data.